Pengaruh Kepemimpinan Transaksional, Lingkungan Kerja, dan Budaya Organisasi terhadap Organizational Citizenship Behavior Pegawai PT PLN UP3 Yogyakarta - Putrii Anggraeni Puspitasari; Prayekti Prayekti; Ignatius Soni Kurniawan (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The research objective was to determine the effect of transactional leadership, work environment, and organizational culture on Organizational Citizenship Behavior. The research method is quantitative, as the population is employees of PT PLN (Persero) UP3 Yogyakarta with saturated sample technique. As for data collection techniques using questionnaires, data analysis techniques with multiple linear regression. The results of the study found that transactional leadership, work environment and organizational culture had a positive and significant effect on Organizational Citizenship Behavior, both partially and simultaneously. Keywords: transactional leadership, work environment, organizational culture, and OCB.